DOES BOARD GENDER DIVERSITY, BOARD SIZE, MANAGERIAL OWNERSHIP AND CAPITAL ADEQUACY RATIO ENHANCE FINANCIAL PERFORMANCE? - Tamboto, Glorrya; Tulung, Joy E.; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study investigates the influence of board gender diversity, board size, managerial ownership, and capital adequacy ratio (CAR) on the financial performance of Indonesian state-owned banks (HIMBARA), focusing on Return on Assets (ROA) as the key performance measure. Utilizing data from financial reports spanning 13 years (2011-2023), the research employs multiple linear regression to assess the relationships between these corporate governance variables and bank performance. The findings reveal that board gender diversity and managerial ownership positively impact financial performance, suggesting that diverse perspectives and managerial stakes enhance decision-making and efficiency. Also, a larger board sizes positively affect performance. Additionally, a higher CAR correlates positively with ROA, underscoring the importance of capital reserves in mitigating risks and boosting profitability. These insights provide valuable guidance for improving governance structures in the banking sector to enhance financial outcomes.    Keyword: Board Gender Diversity, Board Size, Managerial Ownership, Capital Adequacy Ratio, Return On Assets.